Pengaruh Intensitas Penggunaan Hand Phone Terhadap Hasil Belajar Siswa - Hery Setiyawan; Indira Fitri Aisyah; Ifa Ayiyida; Setya Ridia Cahyaning Dewi Tyastuti (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The use of mobile phones by students has become a common thing in daily life. This study aims to analyze the influence of the intensity of mobile phone use on student learning outcomes. The research was conducted using quantitative methods. Data was collected through questionnaires that measured the intensity of mobile phone use, both for academic and non-academic activities, as well as the value of student learning outcomes. The results of the analysis showed that there was a negative correlation between the intensity of mobile phone use for non-academic activities and student learning outcomes, where the higher the intensity of mobile phone use for things outside of learning, the lower the learning outcomes. On the other hand, moderate use of mobile phones for activities that support learning can have a positive impact on learning outcomes. This finding indicates the importance of managing the use of mobile phones wisely by students so as not to interfere with academic achievement.